(untitled) (Archives of Criminology, 2006)
The face of terrorism is changing. Even the motivations do not remain the same as 10–20 years ago. Now, we are facing the emergence of a new category of an offensive gear unknown before. Intelligent networks, telecommunications infrastructure, security procedures and computer equipment once designed and expected to serve and protect people have become terrorist weapons. States and nations are currently almost powerless against this new and destructive phenomenon. The procedures and methods of countering terrorism, which world’s specialists have created and perfected over the past decades, are ineffective against this enemy. That is because this enemy does not attack us with trucks loaded with explosives, neither with dynamite strapped to the bodies of fanatics, nor gas canisters. This enemy attacks us with ones and zeros using our own infrastructure. Nowadays, cyberspace is constantly under assault. Cyber spies, saboteurs, and thrill seekers hack into computer systems, sabotage data and applications, launch computer viruses and worms, steal and trade secrets, conduct fraudulent transactions and what is worse, remotely influence the physical world around us. Unfortunately, the cases where operations of waste dump management system, power grid or telecommunication services were affected, are no longer political fiction. Moreover, these attacks are being facilitated with increasingly powerful and easy-to-use software tools, which are available from many FTP servers in the Internet. The existing threat to water dams, land and air traffic control systems, electric power distribution structure and many other hidden but vulnerabte points of the western civilisation is the nightmare of our times. This paper aims at outlining the main trends of terrorism in our technologically-dependent society. It also presents both the known and potential ways the Internet may serve as a weapon for the next generation of terrorists.